Antibiotic therapy of selected gastrointestinal infections - Kotowska, Maria; Albrecht, Piotr (Przewodnik Lekarza/Guide for GPs, 2008)
This paper presents diagnostic techniques, symptomatology and overall principles of the therapy of selected bacterial infections of the digestive tract in children and adults. The most often they manifest itself in the form of an acute infectious diarrhea. In the case of pregnant women and elderly people this condition requires special attention and the specific therapeutic approach. Campylobacteriosis and yersiniosis belong to frequently present illnesses that required antibiotics. This problem concerns both developing, as well as industrialized countries. Increase of people’s migration is connected to travelers diarrhoea. Towards fast growing resistance to antibiotics, decision on antibiotic therapy should be carefully evaluated.